TARGETED HEALTH INTERVENTIONS TO SAVE MOTHERS, NEWBORNS, AND CHILDREN IN KENYA: A MULTI-FACETED APPROACH INFORMED BY BEHAVIORAL, DEMOGRAPHIC, AND CLINICAL RISK FACTORS - Karanja, Jane Njeri; Kariuki, Samuel Muturi; Mwangi, Grace Wangari (Global Journal of Medical and Health Science, 2023)
This study examines the effectiveness of targeted health interventions aimed at reducing perinatal mortality in Kenya, with a focus on Lurambi and Butere sub-counties in Kakamega County. Using a community-based retrospective cross-sectional research design, mixed methods were employed to investigate the relationship between delays in making timely decisions to seek medical assistance and perinatal mortality. A total of 520 respondents were randomly selected from 40 villages, and data was collected through interviews from November 2017 to March 2018.The findings indicate that maternal education level and employment status significantly influenced perinatal mortality, highlighting the importance of socioeconomic factors in maternal and neonatal health. Factors such as wrong actions taken during antenatal complications, emergency unpreparedness, and lack of recognition of newborn danger signs were significantly associated with perinatal mortality. Birth preparedness and complication readiness during pregnancy and childbirth were identified as key components in reducing delays in obtaining care.This research underscores the critical role of strengthening maternal education and social support systems throughout the continuum of care, from pregnancy to postnatal periods, to ensure newborn survival. These findings contribute valuable insights into maternal and newborn healthcare practices and policy changes that, if implemented, could lead to a significant reduction in perinatal mortalities in Kenya and similar settings. Targeted interventions informed by behavioral, demographic, and clinical risk factors have the potential to transform the healthcare landscape and save the lives of mothers, newborns, and children in Kenya